Padrão de forrageamento de Cebus flavius (Schreber, 1774) (Primates: Cebidae), em um fragmento de Mata Atlântica na Paraíba - Santos, Alinny Costa Araújo dos (2013)
The present study aimed to describe the foraging behavior of a group of Blond Capuchin Monkey, Cebus flavius, of approximately 69 individuals, which inhabits a fragment of Atlantic Forest habitat in the State of Paraíba, and construe the variability of foraging patterns across age and sex classes and between dry and wet seasons. The systematic collection of data was conducted monthly from January to October 2012. Data were collected in the form of 1-min Focal animal sampling, with instantaneous recording every 10 seconds, and 5 minute intervals between sessions. In each session was recorded the types of foraging (Manual foraging, Visual foraging or Extractive foraging), the foraged food, the type and size of foraging supports and the canopy position (vegetation stratum). All-events sampling was used to record food-related agonism in group, which were analyzed in the form of rates per observation hour. Obtained a total of 1436 completes animal focal samples, which totaled 8,616 behavioral records. We observed significant differences in foraging patterns across sex. Females exhibited a higher frequency to Manual foraging, involved in the search for reproductive plant parts and non-reproductive plant parts, in the middle and upper stratum, while males spend more time to prey extractive foraging behavior, over trunks or near ground level. Variations in foraging patterns also occurred across ages classes. The frequency the Extractive foraging behavior, foraging for preys, and use of large substrates increased with age. Differences in foraging patterns were also observed between seasons. During the wet season there was a predominance of Manual foraging for reproductive e non-reproductive plant parts, in the middle and upper stratum of vegetation. By contrast in the dry season there was a significant increase in exploitation of the exotic resources, and preys extractive foraging behavior, near ground level. The food-related agonism in the group studied occurred at a rate of 0.53 episodes per observation hour.There was a significant increase of agonistic conflicts in the dry season. The results of the present study show the ability of individuals in adapt the foraging pattern to seasonal variation in resources availability, and different energy demands related to sex-age, re-emphasizing the behavioral and ecological flexibility characteristic of the genus Cebus.